Innovation Analysis of Birth Certificate Making with Integrated System of 3 Agencies in 1 Service Counter (SI DUKUN 3 In 1) in Improving Service Quality at Jakarta Population and Civil Registry Office - Yulianto, Yulianto; Wahyuni, Yuyun (Technium Social Sciences Journal, 2022)
Abstract. The lack of public understanding of the importance of birth certificates encourages the Jakarta Population and Civil Registry Office to improve public services by making innovations in overcoming the problem of making birth certificates for new-borns in hospitals / hospitals / health centres / clinics. The purpose of this study is to analyse and evaluate the Innovation of Making Birth Certificates with an Integrated System of 3 Agencies in 1 Service Counter (SI DUKUN 3 in 1) in Improving Service Quality at the Jakarta Population and Civil Registry Office in terms of innovation attributes, namely Relative Advantage, Compatibility, Complexity, Triability and Observability, supporting factors and inhibiting factors as well as efforts made to improve the quality of services at Jakarta Population and Civil Registry Office. This study uses a qualitative method with a descriptive approach. Data was collected by interview, observation, and documentation review. The data analysis technique uses data reduction, data presentation and conclusion drawing. The results of this study indicate that the innovation of Making Birth Certificates with an Integrated System of 3 in 1 Service Counter (SI DUKUN 3 in 1) is viewed from the innovation attribute Relative Advantage, Compatibility, Triability and Observability are good, but unfortunately they still have complexity in the form of network errors, lack of socialisation. There are supporting factors, namely the presence of competent employees, a spirit of service and a spirit of collaboration, leadership that encourages innovation and a strong organisational structure. In addition, there are inhibiting factors, namely excessive dependence on high performers and administrative barriers.